AC Signal Analysis of Bionanosensors for Intermediate Frequency Range - Desai, Vishal; Sinha, Saion (New Ideas Concerning Science and Technology Vol. 6, 2021)
Nanobiosensors are devices which incorporate nanomaterials to detect miniscule quantities of biological and chemical agents. The authors have developed novel Bionanosensors (BNS) for quick, efficient and precise detection of bacterial pathogens using the principles of Carbon Nano Tubes (CNT)-Deoxyribonucleic acid (DNA) interactions and DNA hybridization. The detection ability of the (BNS) was observed to be independent of the initial sensor resistance. This conclusion implies that BNS’s performance is independent on the method of fabrication. Two new methods, such as Low Pass Filter (LPF) and Curve Fitting (CF) were developed for analyzing the sensing mechanisms of BNS. These methods successfully modeled the performance of the BNS. In addition, the evidence is provided to elucidate the success of the model which can explain the DNA hybridization on the sensor surface. These models successfully demonstrated the detection of DNA hybridization versus non-hybridization. Thus, the models not only assist in providing insight of these BNS but can also be used to analyze other similar nanoscale devices which enhances the applicability of these modeling methods.